A high content screening assay for discovery of antimycobacterial compounds based on primary human macrophages infected with virulent Mycobacterium tuberculosis. (July 2022) - Kalsum, Sadaf; Otrocka, Magdalena; Andersson, Blanka; Welin, Amanda; Schön, Thomas; Jenmalm-Jensen, Annika; Lundbäck, Thomas; Lerm, Maria
Abstract: Drug resistance in Mycobacterium tuberculosis is an emerging threat that makes the discovery of new candidate drugs a priority. In particular, drugs with high sterilizing activity within host cells are needed to improve efficacy and reduce treatment duration. We aimed to develope and validate a High Content Screening assay based on Mycobacterium tuberculosis -infected primary human monocyte-derived macrophages as its natural reservoir. Infected primary human monocyte-derived macrophages were exposed to control antibiotics or tested compounds on 384 well plates. Intracellular bacterial growth and macrophage numbers were evaluated using an ImageXpress High Content Screening system and Z′-factor was calculated to assess the reproducibility. The combination of isoniazid and rifampicin as a positive control rendered a Z′-factor above 0.4, demonstrating suitability of the assay for screening and compound profiling purposes. In a validation experiment, isoniazid, rifampicin, moxifloxacin and levofloxacin all effectively inhibited intracellular growth as expected. Finally, a pilot screening campaign including 5700 compounds from diverse libraries resulted in the identification of three compounds with confirmed antimycobacterial activity in the low micromolar range and low host cell toxicity. The assay represents an attractive screening platform for both academic research on host-pathogen mechanisms in tuberculosis and for the identification and characterization of novel antimycobacterial compounds. Highlights: Compounds screening using M. tuberculosis infected macrophages provided information of cell viability and bacterial growth. Assay validated with approved TB drugs rendered dose-response information for these drugs in a physiologically relevant setting. Testing of >5000 compounds resulted in identification of an isoniazid enamine and two promising lead structures.